Effect of acute exposure to moderate altitude on muscle power: Hypobaric hypoxia vs. normobaric hypoxia - Feriche, B.; Garcia-Ramos, A.; Calderon-Soto, C.; Drobnic, F.; Bonitch-Gongora, J. G.; Galilea, P. A. (PLOS ONE, 2014)
When ascending to a higher altitude, changes in air density and oxygen levels affect the way in which explosive actions are executed. This study was designed to compare the effects of acute exposure to real or simulated moderate hypoxia on the dynamics of the force-velocity relationship observed in bench press exercise. Twenty-eight combat sports athletes were assigned to two groups and assessed on two separate occasions: G1 (n = 17) in conditions of normoxia (N1) and hypobaric hypoxia (HH) and G2 (n = 11) in conditions of normoxia (N2) and normobaric hypoxia (NH). Individual and complete force-velocity relationships in bench press were determined on each assessment day. For each exercise repetition, we obtained the mean and peak velocity and power shown by the athletes. Maximum power (Pmax) was recorded as the highest Pmean obtained across the complete force-velocity curve. Our findings indicate a significantly higher absolute load linked to Pmax (~3%) and maximal strength (1RM) (~6%) in G1 attributable to the climb to altitude (P<0.05). We also observed a stimulating effect of natural hypoxia on Pmean and Ppeak in the middle-high part of the curve (=60 kg; P<0.01) and a 7.8% mean increase in barbell displacement velocity (P<0.001). No changes in any of the variables examined were observed in G2. According to these data, we can state that acute exposure to natural moderate altitude as opposed to simulated normobaric hypoxia leads to gains in 1RM, movement velocity and power during the execution of a force-velocity curve in bench press.